2018
DOI: 10.1002/app.47316
|View full text |Cite
|
Sign up to set email alerts
|

Development of whey protein isolate/polyaniline smart packaging: Morphological, structural, thermal, and electrical properties

Abstract: Development of smart packaging from biodegradable polymers that allow monitoring food exposure conditions is important to reduce food and material packaging waste. The objective of this article is to evaluate the conductivity of polyaniline (PANI) in its doped form with dodecylbenzene sulfonic acid on morphological, structure, thermal, and electrical (Hall effect) properties of whey protein isolate (films. Films show immiscible with 10−3 S cm−1 conductivity and semiconductor behavior due to a phase separation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 36 publications
2
28
0
Order By: Relevance
“…The main absorption peaks of WPI were between 500 and 750 cm −1 and related to the absorption of glycerol bonds; peaks between 900 and 1,150 cm −1 corresponded to the N H bonds and C H stretching (type III amide); peaks between 1,400 and 1,550 cm −1 corresponded to the N H stretching (type II amide); peaks between 1,600 and 1,700 cm −1 were related to the C O and C N stretching vibrations (type I amide), which showed a decrease in the band intensity with the increase in LMP concentration (R.A. Carvalho et al, 2019;de Oliveira et al, 2018;Hammann & Schmid, 2014;Núñez-Flores et al, 2013). This region is related to the presence of secondary proteins that lose their conformation during heating of the film-forming solutions, forming other interactions with the constituents, thus leading to a decrease in the bands characteristic of the initial structure.…”
Section: Ftir Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The main absorption peaks of WPI were between 500 and 750 cm −1 and related to the absorption of glycerol bonds; peaks between 900 and 1,150 cm −1 corresponded to the N H bonds and C H stretching (type III amide); peaks between 1,400 and 1,550 cm −1 corresponded to the N H stretching (type II amide); peaks between 1,600 and 1,700 cm −1 were related to the C O and C N stretching vibrations (type I amide), which showed a decrease in the band intensity with the increase in LMP concentration (R.A. Carvalho et al, 2019;de Oliveira et al, 2018;Hammann & Schmid, 2014;Núñez-Flores et al, 2013). This region is related to the presence of secondary proteins that lose their conformation during heating of the film-forming solutions, forming other interactions with the constituents, thus leading to a decrease in the bands characteristic of the initial structure.…”
Section: Ftir Analysismentioning
confidence: 99%
“…Whey protein isolate (WPI) has the ability to form films, it is transparent and it has excellent oxygen permeability. These factors are one of several make possible studies with WPI for the replacement of conventional plastics (de Oliveira, Ugucioni, da Rocha, & Borges, 2018;Galus & Lenart, 2019;Hammam, 2019;Semenova et al, 2020;Solghi, Emam-Djomeh, Fathi, & Farahani, 2020;Zhan, Dai, Zhang, & Gao, 2020). Besides that, the WPI is a by-product of the cheese industry composed mainly of β-lactoglobulin, α-lactoalbumin, serum albumin, and immunoglobulin, and its composition can vary according to the coagulation method used in the cheese-making process.…”
mentioning
confidence: 99%
“…In addition, there is a growing use of these biopolymers in the development of packaging biodegradable as an alternative to the use of polymers from non-renewable sources for application in food packaging. The most widely studied polymers for this purpose are chitosan, pectin, starch, polylactic acid, whey protein isolate and cellulose (Assis et al, 2020;Carvalho et al, 2019; Cerqueira et a., 2011; de Castro e Silva et al, 2019;de Oliveira et al, 2018;de Oliveira et al, 2019;Porta et al, 2011;Silva et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…710 Kaur et al 2018 synthesized nanoreinforced green bionanomaterials from chicken feather keratin proteins and suggested for multiple commercial applications. 10 Another study is reported by de Oliveira and co-workers in 2019 prepared biopolymer films from a by-product of cheese industry. That is, whey protein isolates as a smart packaging to prevent the changes in conductivity of the food.…”
Section: Introductionmentioning
confidence: 99%
“…That is, whey protein isolates as a smart packaging to prevent the changes in conductivity of the food. 10…”
Section: Introductionmentioning
confidence: 99%